A bibliographic study on big data: concepts, trends and challenges. Issue 3 (5th June 2017) - Mishra, Deepa; Luo, Zongwei; Jiang, Shan; Papadopoulos, Thanos; Dubey, Rameshwar
Abstract : Purpose: The purpose of paper is twofold. First, it provides a consolidated overview of the existing literature on "big data" and second, it presents the current trends and opens up various future directions for researchers who wish to explore and contribute in this rapidly evolving field. Design/methodology/approach: To achieve the objective of this study, the bibliographic and network techniques of citation and co-citation analysis was adopted. This analysis involved an assessment of 57 articles published over a period of five years (2011-2015) in ten selected journals. Findings: The findings reveal that the number of articles devoted to the study of "big data" has increased rapidly in recent years. Moreover, the study identifies some of the most influential articles of this area. Finally, the paper highlights the new trends and discusses the challenges associated with big data. Research limitations/implications: This study focusses only on big data concepts, trends, and challenges and excludes research on its analytics. Thus, researchers may explore and extend this area of research. Originality/value: To the knowledge of the authors, this is the first study to review the literature on big data by using citation and co-citation analysis.